Life Balance and Work Addiction Among NCAA Administrators and Coaches. Issue 3 (2nd September 2019) - Hancock, Meg G.; Balkin, Richard S.; Reiner, Summer M.; Williams, Sarah; Hunter, Quentin; Powell, Brent; Juhnke, Gerald A.
Abstract : Intercollegiate athletics represent an industry prone to challenges of work addiction and life balance. Work addiction and life balance domains in male and female intercollegiate athletic coaches and administrators ( N = 245) were examined using multiple regression analysis. Higher levels of stress/anxiety, sleep disturbance, and career satisfaction and lower levels of quality of relationships and friendships were the strongest predictors of work addiction. Counseling focused on reducing the negative aspects of work addiction, while maintaining job performance, may benefit this population.